FUZZY NEURAL NETWORK DENGAN NEURON FUZZYKWAN DAN CAI SERTA APLIKASINYA UNTUK EVALUASI KINERJA PERTAHANAN KLUB SEPAK BOLA - Deri Januar; Mutia Nur Estri (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2013)
In this paper, we discuss fuzzy neural network with neuron fuzzy Kwan dan Cai. The algorithm used in this fuzzy neural network is the feed forward algorithm. Futhermore, fuzzy neural network with neuron fuzzy Kwan and Cai can be applied to evaluate a defense performance of football clubs. In this application, we do calculation manually and using a program.